The PEMANFAATAN DANA ZAKAT UNTUK MODAL USAHA DENGAN AKAD QARD KAJIAN FATWA DEWAN SYARI'AH NASIONAL NO:19/DSN-MUI/IV/2001 TENTANG AL-QARDH - Margareth Aliyatul Maimunah; Setiawan bin Lahuri (KASBANA, 2025)
Zakat plays a vital role in poverty alleviation and community welfare. Beyond consumptive uses, zakat can be productively channeled for mustahik business financing through qardh (interest-free loan) schemes, guided by DSN-MUI Fatwa No. 19/DSN-MUI/IV/2001. This literature review aims to examine how zakat funds can be utilized as business capital via qardh contracts. The study adopts a literature review method by examining relevant fatwas, books, and academic journals. The findings indicate that qardh provides equitable funding, prevents beneficiaries from exploitative financial systems, and fosters sustainable zakat distribution as returned funds can be re-utilized. The qardh contract also proves more effective than grants in fostering responsibility and entrepreneurship. However, implementation faces challenges like low repayment rates (only 20% on time), weak mustahik managerial capacity, and insufficient continuous supervision. Implications suggest the need for entrepreneurship training, intensive mentoring, and integrated monitoring. Strong collaboration among zakat institutions, government, and the community has the potential to make zakat utilization through qardh a strategic solution for sustainable economic empowerment of the Muslim community. Keywords: Productive Zakat, Qardh Contract, DSN-MUI Fatwa, Economic Empowerment, Mustahik.